Hepatitis B Antigen Inhibitor in Human Faeces and Intestinal Mucosa. Issue 5862 (12th May 1973) - Piazza, M.; Stasio, G. Di; Maio, G.; Marzano, L. A.
Abstract : Hepatitis B antigen (HB Ag) positive sera became negative after in-vivo incubation with homogenates of human faeces or intestinal mucosa. This was found to occur in all sera tested by various methods. These findings suggest the existence in the human intestine of a substance able to inactivate the HB Ag and that it is not an antibody or of the nature of interferon. The presence of an inhibitor could explain why B-type hepatitis is seldom if ever faecally transmitted and also the low oral infectiousness of the B virus.